2017
DOI: 10.1103/physrevb.96.045427
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic modeling of tunable graphene-based terahertz Landau-level lasers

Abstract: In the presence of strong magnetic fields the electronic bandstructure of graphene drastically changes. The Dirac cone collapses into discrete non-equidistant Landau levels, which can be externally tuned by changing the magnetic field. In contrast to conventional materials, specific Landau levels are selectively addressable using circularly polarized light. Exploiting these unique properties, we propose the design of a tunable laser operating in the technologically promising terahertz spectral range. To uncove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…1b). However, to the best of our knowledge, no cyclotron emission, let alone the Landau level laser based on graphene, has been reported so far, despite pertinent theoretical predictions and numerous experimental attempts 10,[20][21][22][23][24][25][26] .…”
mentioning
confidence: 99%
“…1b). However, to the best of our knowledge, no cyclotron emission, let alone the Landau level laser based on graphene, has been reported so far, despite pertinent theoretical predictions and numerous experimental attempts 10,[20][21][22][23][24][25][26] .…”
mentioning
confidence: 99%
“…Recent studies of the nonlinear responses have been extended to wavelengths in the infrared. [2][3][4][5][6][7] A huge optical susceptibility is predicted by Yao and Belyanin 3,4 and confirmed by the four wave mixing (FWM) experiments of König-Otto et al in the far infrared. 5 Proposed applications for graphene-based photonics include the generation of entangled photons, 8 an all-optical switch, 9 tunable lasers, 6 the dynamic control of coherent pulses, 10 and the demonstration of optical bistability and optical multistability.…”
Section: Introductionmentioning
confidence: 95%
“…[2][3][4][5][6][7] A huge optical susceptibility is predicted by Yao and Belyanin 3,4 and confirmed by the four wave mixing (FWM) experiments of König-Otto et al in the far infrared. 5 Proposed applications for graphene-based photonics include the generation of entangled photons, 8 an all-optical switch, 9 tunable lasers, 6 the dynamic control of coherent pulses, 10 and the demonstration of optical bistability and optical multistability. 11,12 Theoretically, optical nonlinearities are mostly studied in an equation-of-motion framework, where solutions of the dynamical equations can be obtained in the rotating wave approximation (RWA) 3,4 or in perturbation method.…”
Section: Introductionmentioning
confidence: 95%
“…Due to the relativistic properties of low-energy electrons in graphene, the spacing between its lowest LLs is extremely large compared to conventional materials. Magnetic fields of a few Tesla give rise to LL transition energies ranging from the terahertz (THz) up to the far-infrared spectral ranges, which makes Landau-quantized graphene a highly promising material for the realization of tunable THz emitters and absorbers [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In previous work [10] we have shown that the remarkable properties of Landau-quantized graphene can be exploited to achieve continuous-wave lasing with an optically pumped population inversion (PI) between neighboring LLs. However, the optical excitation is highly challenging since one has to selectively address single LLs with energetic separations of a few tens of meV.…”
Section: Introductionmentioning
confidence: 99%